PENGARUH AKUN INSTAGRAM @WONDERFULINDONESIA TERHADAP KEPUTUSAN PERJALANAN WISATA PADA MASA NEW NORMAL BAGI GENERASI Z - Khadijah, Amirah Siti; Samatan, Nuriyati; Prihantoro, Edy (JURNAL BADATI, 2024)
This study aims to determine the effect of the @wonderfulindonesia Instagram account on travel decisions during the new normal period for generation Z. The theory used in this study is the Uses and Gratifications theory. This research is a quantitative study and uses a questionnaire as a data collection tool. The data analysis technique used is the Normality Test, Linearity Test, Simple Linear Regression Test, T-Test, and R Square Test, then the data is processed using SPSS software version 26.0. The results of this study indicate that the R number (correlation number) is 11.1% of the influence of the @wonderfulindonesia Instagram account on travel decisions during the new normal period for generation Z. Based on the results of the hypothesis test (t-test) it can be concluded that t count t table which means Ho was rejected and Ha was accepted, which meant that the @wonderfulindonesia Instagram account had an influence on travel decisions during the new normal period for generation Z.